A Case of Malignant Peripheral Nerve Sheath Tumor of the Hypoglossal Nerve after Stereotactic Radiosurgery Treatment - Yang, Tong; Juric-Sekhar, Gordana; Born, Donald; Sekhar, Laligam N. (Journal of Neurological Surgery Reports, 2014)
Objectives Hypoglossal schwannomas are rare. Surgical resection has been the standard treatment modality. Radiosurgery has been increasingly used for treatment. Radiation-associated secondary malignancy/malignant transformation has not been documented in the literature for the treatment of nonvestibular schwannomas.Setting The patient was a 52-year-old man with an enlarging high cervical/skull base lesion 8.5 years after CyberKnife treatment of a presumed vagal schwannoma. A decision was made for surgical resection, and the tumor was found to originate from the hypoglossal nerve intraoperatively. Final pathology diagnosis was malignant peripheral nerve sheath tumor.Results Patient had a gross total resection. Three months after resection, he received fractionated radiation of 50 Gy in 25 fractions and a boost gamma knife radiosurgery of 10 Gy to the 50% isodose surface. He remained tumor free on repeat magnetic resonance imaging 9 months after the resection.Conclusion Although extremely rare, radiation treatment of nonvestibular schwannomas can potentially cause malignant transformation.
Keywords: malignant peripheral nerve sheath tumor; nonvestibular schwannoma; radiation associated malignancy; stereotactic radiosurgery